View of dry friction in vibration analysis even blades with disorder frequency - Зіньковський, А.П.; Астанін, В.В.; Дроздов, Р.І. (Proceedings of National Aviation University (archive), 2006)
The paper presents results of numerical experiments involving the determination of the influence of dry friction due to displacement of contact surfaces on the formation of vibration of pairs of blades with mistuning of their frequencies. It is shown that dry friction compared to viscous one induces no qualitative changes in the character of t he resonant vibration amplitude versus blade frequency mistuning relation but results in some quantitative changes.